Practical Points for Using Contrast Media - Suriyajakryuththana, Wiboon; Suppakool, Noppagao (Vajira Medical Journal : Journal of Urban Medicine, 2016)
This is a review article for updating knowledge about contrast media. Both Iodinated contrast media and contrast media for MRI are presented. It provides advantage and disadvantage of the contrast media for clinicians, radiologists and caregivers in department of radiology. The main focuses are to improve patient’s safety and enhanced accuracy after the contrast media use.